Physical variables of d = 3 Maxwell-Chern-Simons theory by symplectic projector method - Helayel-Neto,J. A. (2006)
The Symplectic Projector Method is applied to derive the local physical degrees of freedom and the physical Hamiltonian of the Maxwell-Chern-Simons theory in d = 1+2. The results agree with the ones obtained in the literature through different approaches.